Strategies for Handling Delays in Building Projects (Private) during the Construction Period in Badung Regency - Juliarta, I Wayan Tedi; Yana, Anak Agung Gde Agung; Dewi, Agung Diah Parami (Journal of Asian Multicultural Research for Economy and Management Study, 2024)
Delay in construction projects is the inaccuracy of completion time in each activity or overall project activity that exceeds the time limit in the contract document.From the results of observations and interviews with several contractors who carry out building construction work, especially privately owned in Badung Regency, where the results show that there are still many projects that experience delays in implementation. This study aims to analyze what factors are dominant in causing delays and provide an overview of strategies for handling project delays during the construction period.Data collection using a questionnaire survey method. The research population was 16 building construction projects that were under construction in Badung Regency starting from 2022 - 2023 with 64 respondents. The data analysis method used is the Relative Importance Index (RII) method and hierarchical clustering in analyzing the dominant factors causing delays then focus group discussion (FGD) is used to help collect and provide information in discussions for the formulation of SWOT analysis. The priority strategy recommended for the project delay handling strategy is the WT strategy which explains the position of the defensive strategy in minimizing internal weaknesses and external threats so that the contractor as the project manager must be able to minimize existing weaknesses in the project and overcome threats in project implementation. While the recommended alternative strategies are WO, ST and SO strategies..